2010
DOI: 10.1038/cgt.2009.86
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of horseradish peroxidase with indole-3-acetic acid and 5-bromoindole-3-acetic acid for gene therapy of cancer

Abstract: Gene-directed enzyme prodrug therapy is a form of targeted cancer therapy, in which an enzyme is used to convert a non-toxic prodrug to a cytotoxin within the tumor. Horseradish peroxidase (HRP) is able to convert the indole prodrugs indole-3-acetic acid (IAA) and the halogenated derivative 5-bromo-IAA (5Br-IAA) to toxic agents able to induce cell kill in vitro. This study characterized HRP-directed gene therapy in vivo. Human nasopharyngeal squamous cell carcinoma cells, FaDu, stably expressing HRP were grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
0
26
1
1
Order By: Relevance
“…Mice in the Ad‐C6‐hTERT‐HRP plus IR group also had longer survival compared with controls. A recent study characterized the HRP/IAA system in vivo for gene therapy and indicated that HRP‐expressing tumors had a modest growth delay when treated with IAA compared with drug vehicle controls, but the treatment response could not be improved by combining HRP‐directed gene therapy with fractionated radiotherapy 29. However, in the current study, we demonstrated that the combination of gene therapy mediated by chimeric promoters with radiotherapy increased the antitumor effect.…”
Section: Discussioncontrasting
confidence: 55%
“…Mice in the Ad‐C6‐hTERT‐HRP plus IR group also had longer survival compared with controls. A recent study characterized the HRP/IAA system in vivo for gene therapy and indicated that HRP‐expressing tumors had a modest growth delay when treated with IAA compared with drug vehicle controls, but the treatment response could not be improved by combining HRP‐directed gene therapy with fractionated radiotherapy 29. However, in the current study, we demonstrated that the combination of gene therapy mediated by chimeric promoters with radiotherapy increased the antitumor effect.…”
Section: Discussioncontrasting
confidence: 55%
“…The total combined daily dose of IAA for a 20 g mouse drinking 3 ml of IAA water (75 mg/kg) and receiving a 0.2 ml IAA gavage (125 mg/kg) was 200 mg/kg. This dose was selected since mice can tolerate up to 200 mg/kg/day IAA without obviously affecting health or body weight (Tupper et al, 2010). The number of mice per group (n) and experimental trials (N) was based on a historical precedent for establishing survival curves for virulent strains of T. gondii in mice (Su et al, 2002).…”
Section: Star Methodsmentioning
confidence: 99%
“…As a model we loaded horseradish peroxidase (HRP) into the cavities of PMOXA 6 ‐PDMS 44 ‐PMOXA 6 polymersomes that contained the bacterial outer membrane protein F (OmpF) in the membrane to control passage of specific substrates and products. We selected HRP because of its biological role in detoxification of H 2 O 2 , known as toxic by‐products of mitochondrial respiration in eukaryotic cells, and its role in modulating the protein function of by thiol oxidation . More recently, HRP has also gained significant interest in cancer research.…”
Section: Mf With Architecture and Functionality As Cell Mimicsmentioning
confidence: 99%